Angielskie nazwy zawodów w polskich serialach obyczajowych - Kaczmarek, Anna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
This article discusses borrowings from English related to the theme aspect of profession names including those adapted in Polish and those typical of professional dialects and formerly not recorded in any lexicographic sources. The research material includes dialogues extracted from Polish serial dramas (referred to by the author as advance serial dramas).The excerpted borrowings from English are primarily oriented to business, media or advertising. This type of words can function in the Polish language because of the language’s nominal need. While many English words referring to professions are used chiefly in social dialects, more and more frequently they tend to be absorbed by general Polish.